2009
DOI: 10.1167/iovs.08-2368
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Regulation of Cationic Amino Acid Transporters in Healthy and Diseased Ocular Surface

Abstract: These results show for the first time the distribution of hCATs in tissues of the ocular surface and lacrimal apparatus. Both transporters seem to be differently regulated under pathologic conditions of the ocular surface. Their physiological functions in amino acid transport make them potential candidates for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…Interestingly, decreased levels of arginine were found to be correlated with a decrease in methionine as a taurine precursor and taurine levels in tears in the course of ocular surface diseases [31]. The inflammatory decrease of arginine levels fits well with an observed upregulation of human cationic transporters 1 and 2 expression under ocular surface disease conditions leading to an increased arginine transport into epithelial cells of the cornea [83]. Since arginine, methionine and taurine levels cohere under disease condition a correlation of their transport of these amino acids during inflammation can be assumed [31].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, decreased levels of arginine were found to be correlated with a decrease in methionine as a taurine precursor and taurine levels in tears in the course of ocular surface diseases [31]. The inflammatory decrease of arginine levels fits well with an observed upregulation of human cationic transporters 1 and 2 expression under ocular surface disease conditions leading to an increased arginine transport into epithelial cells of the cornea [83]. Since arginine, methionine and taurine levels cohere under disease condition a correlation of their transport of these amino acids during inflammation can be assumed [31].…”
Section: Discussionsupporting
confidence: 53%
“…In HepG2 cells this effect could be proven as an adaptive regulation activation of a high-affinity taurine transporter system [80,81]. Besides taurine, L-arginine is a well studied amino acid involved in immune response [82,83]. Interestingly, decreased levels of arginine were found to be correlated with a decrease in methionine as a taurine precursor and taurine levels in tears in the course of ocular surface diseases [31].…”
Section: Discussionmentioning
confidence: 99%
“…CAT2A and CAT2B). The expression of CAT2B is observed in many different cell types under inflammatory conditions, and CAT2A exhibit a 10-fold lower substrate affinity [40]. Although CAT2 is important for the transport of L-arginine through the cell membrane, a recent epidemiologic study reported that the expression of SLC7A1 , not SLC7A2 , was significantly elevated in colorectal cancer tissues among colorectal cancer patients[11].…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β (10 ng/ml; Immunotools, Friesoythe, Germany) and/or TNFα (10 ng/ml; Immunotools), lipopolysaccharide (LPS) (500 ng/ml; Santa Cruz Biotechnology, Heidelberg, Germany), peptidoglycan (10 ng/ml; Santa Cruz Biotechnology), or supernatants of Pseudomonas aeruginosa (1:100) or Staphylococcus aureus (1:15) were added 3 hours later, and incubation was continued for 24 hours. Bacteria were produced as recently described (13).…”
Section: Methodsmentioning
confidence: 99%